The economics of oil-seed crops for energy use: a case study in an agricultural European region - Robles, Rita (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2011)
There’s a strong link between the production of biofuels and energy crops. The first of these activities may contribute to the appearance of new products in agriculture, besides giving a boost to activities such as provision of services and aiding in the diversification of economic activities in rural areas. Farmers’ final decision to include energy crops into or exclude them from their productive alternatives depends on various factors of a different nature (political, legal, technical, economic or socio-cultural). This paper analyzes the socio-economic aspects related to the introduction of oil-seeds (sunflower and rape seed) as energy crops in one of the most important agricultural regions in Spain (Castile and Leon). Thus, using RRA (Rural Rapid Appraisal) and the Economic Accounts for Agriculture (EAA), the study provides an evaluation of the main economic accounts of these crops and an idea of their profitability, impact on the level of employment and environmental consequences